The laws of attraction - Connealy, Mary (Connealy, Mary. Wyoming sunrise, 2023)
"If widowed seamstress Nell Armstrong has to make one more pair of boring chaps for the cowboys in her tiny Wyoming town, she might just quit the business altogether! So meeting Brand Nolte, a widower struggling to raise three girls on his own, seems like her dream come true. Brand has no idea how to dress the girls properly, and Nell finally has a chance to create beautiful outfits while also teaching the girls to sew. But Nell is much more than a seamstress, and the investigative skills and knowledge she picked up alongside her late lawman husband soon become critical when a wounded stagecoach-robbery survivor is brought to town. As danger closes in from all sides, Nell and Brand must discover who has a target trained on them before it's too late"--